DESIGN OF AUTOMATIC BOTTLE FILLING AND SEALING SYSTEM WITH QUALITY CONTROL - Muhammad Lucky Harvi; Ni Putu Devira Ayu Martini; Subekti Ari Santoso3; Riski Adi Saputro; Bintang Birrul Walidaina (Universitas Tarumanagara, 2025)
This research aims to design an automated bottle filling and capping system based on a Programmable Logic Controller (PLC) to improve production efficiency and accuracy in the liquid packaging industry. The system operates automatically from bottle detection, filling process, cap placement and sealing, to sorting bottles based on quality and standard. PLC is used to read sensors, control actuators, and regulate timing between each stage to ensure that the workflow runs in a synchronized and consistent manner. Counters are applied to limit the number of bottles in one production cycle and support automatic product classification, allowing the system to maintain structured output throughout the manufacturing process. The implementation results show that the system is able to run the entire process stably, precisely, and without manual intervention. The designed ladder diagram covers all major control aspects, including I/O mapping, sorting logic, actuator coordination, and production batch management. Additionally, the system integrates multiple types of sensors to detect defects, ensuring that only products meeting the required standards proceed to the next stage. This system is modular, cost-effective, and suitable for small to medium-sized industries that require efficient automation solutions. With this approach, the system is able to significantly reduce human error, enhance production consistency, and maintain product quality standards while optimizing overall operational performance. Furthermore, the system architecture is structured to ensure ease of modification and scalability, enabling future expansion or integration with additional equipment as production demands evolve. These characteristics strengthen the system’s applicability in modern industrial environments that increasingly rely on adaptive and intelligent automation technologies. ABSTRAK: Penelitian ini bertujuan untuk merancang sistem otomatis pengisian dan penyegelan botol berbasis Programmable Logic Controller (PLC) guna meningkatkan efisiensi, akurasi, serta konsistensi proses produksi pada industri pengemasan cairan. Sistem ini dirancang untuk beroperasi secara penuh otomatis, dimulai dari tahap deteksi keberadaan botol, proses pengisian cairan, pemasangan dan penyegelan tutup, hingga proses pemilahan botol berdasarkan kualitas dan standar produksi yang telah ditetapkan. PLC digunakan sebagai pusat kendali untuk membaca sinyal dari berbagai sensor, mengaktifkan aktuator secara terkoordinasi, serta mengatur waktu antarproses agar setiap tahapan berjalan stabil, terstruktur, dan sinkron. Selain itu, counter diterapkan untuk membatasi jumlah botol dalam satu siklus produksi sehingga alur kerja lebih terkendali dan proses klasifikasi produk dapat dilakukan secara sistematis. Hasil implementasi menunjukkan bahwa sistem mampu menjalankan seluruh rangkaian proses secara stabil, presisi, dan tanpa intervensi manual. Diagram ladder yang dirancang mencakup seluruh aspek utama pengendalian, mulai dari pemetaan input/output (I/O), logika pendeteksian cacat, koordinasi aktuator, hingga manajemen batch produksi. Dengan desain yang bersifat modular, fleksibel, dan hemat biaya, sistem ini sangat sesuai diterapkan pada industri kecil hingga menengah. Selain itu, integrasi berbagai jenis sensor—meliputi sensor fotoelektrik, induktif, dan sensor visi—memungkinkan proses deteksi yang lebih menyeluruh sehingga setiap variasi kondisi pada botol dapat diidentifikasi secara cepat dan akurat. Sistem juga dirancang agar mudah diperluas dan dimodifikasi, memungkinkan penambahan fungsi baru atau integrasi dengan perangkat otomasi lainnya. Dengan karakteristik tersebut, sistem ini mampu memberikan kontribusi signifikan dalam penerapan otomasi yang lebih andal dan adaptif pada lingkungan produksi modern